Impacts of economic freedom and language on technology transfer in developing countries - Tee, Chee Lip (2016)
This dissertation consists of three empirical exercises, all of which are assessments of issues related to the transfer of technology in developing countries. The first objective of this dissertation is to examine the role of economic freedom in moderating research and development (R&D) spillovers from developed to developing countries. Two channels are analyzed, namely import and international student flows. The empirical results based on generalized method-of-moment system estimation using data from a panel of 75 developing countries show that spillover effects through import and international student flow are significant, but the latter channel appear to be more important in term of magnitude. This finding is consistent with view that technology diffusion via human capital mobility should not be underestimated. More importantly, the finding reveals that countries with higher level of economic freedom benefit more from R&D spillovers. This provides further support to the idea that successful knowledge acquisition requires that host countries have the ability to absorb and internalise new technology (i.e. absorptive capacity). The second objective is to investigate the influence of technology transfer on innovation activity in developing countries. The Extreme-Bound-Analysis (EBA) approach is applied to data from 58 developing countries over the 1996 - 2011 period. The result reveals that human capital is a robust determinant of innovation activity. Meanwhile, the impact of foreign technology inflow is found to be different depending on the variables used in the analysis. Specifically, the results indicate that import of machinery and equipment affects domestic innovation activity positively but total import, import of manufactured goods, and FDI inflows appear to be fragile determinants of innovation activity in developing countries. Accordingly, the results suggest that import of machinery and equipment is expected promote productivity through its impact on domestic innovation activity.Finally, the third objective is to evaluate whether proficiency in English language will enhance the spillover effects from foreign direct investment. This objective is motivated by previous studies which show that countries with mutual language enjoy lower trade cost and increased trade volume. Nevertheless, common native language between countries is not common and studies suggest that English language is widely used in international activity. In order to test this hypothesis, a threshold regression is employed using data from 61 developing countries over the 1976-2013 period. The findings reveal that host country with greater level of English proficiency benefit more from the foreign direct investment (FDI) inflows. Obviously, language plays an important role in the transfer of technology via FDI. This also suggests that the proficiency English language is an important part of the host country’s absorptive capacity. The overall findings indicate the significance of absorptive capacity in technology transfer (i.e. economic freedom and English language proficiency) as it could enhance the benefit gain by host country. Besides, technology transfer does not only benefit economic performance through enhance productivity among developing countries, but it also stimulate domestic innovation effort, which in turn contribute to growth in the long run.